Glässer’s disease in swine from Northeastern Brazil - Bom,Hisadora A.S.C. (2020)
ABSTRACT: Glässer’s disease is an important infectious disorder of swine caused by Haemophilus parasuis. Although well recognized in most regions of Brazil, outbreaks of Glässer’s disease have not been described in Northeastern region. For this reason, three municipalities of the Pernambuco State were visited in order to identify histories of high mortality in growing and finishing pigs. The main clinical signs consisted of dry cough, apathy, fever, anorexia, paresis, muscle tremors, motor incoordination, seizures leading to high mortality rates. Nine pigs were necropsied, and fragments of the nervous system, organs of the abdominal and thoracic cavities were collected for histological analysis. In addition, lung and brain fragments were used for DNA extraction and molecular testing by real-time Polymerase Chain Reaction (PCR). Grossly, the main lesions consisted of petechial hemorrhages or ecchymosis on the skin of the face, abdomen, forelimbs, and hind limbs. The main severe lesions consisted of hydropericardium, hemopericardium, fibrinous pericarditis and pleuropneumonia. Microscopically, pericarditis, epicarditis and subepicardial myocarditis, followed by a moderate to severe multifocal pleuropneumonia, fibrinosuppurative and necrotizing were the most frequent lesions observed. Real-time PCR amplified H. parasuis infB gene in all samples analyzed, confirming the presence of this etiologic agent.